Development of Indirect Sandwich ELLA for Detection of Insects in Food - Matej Pospiech; Martina Pečová; Marie Bartlová; Zdeňka Javůrková; Anežka Kopecká; Kateřina Šebelová; Ondřej Pospíšil; Martin Kulma; Jakub Folke; Bohuslava Tremlová; Lenka Kouřimská; Jana Hajšlová (Applied Sciences)
Edible insects have been officially classified as food in the European Union since 2015. Currently, four insect species are approved for food use. However, no official method for detecting insects in food has been recognized to date. To establish a simple analytical method for insect detection in food, we developed an indirect sandwich (enzyme-linked lectin sorbent assay) ELLA specific for N-acetylglucosamine in chitin and chitosan polymers. The validation of the method demonstrated that the ELLA developed in this study is reliable for insect detection. The limit of detection (LOD) and quantification (LOQ) were 0.006 and 0.028 mg/mL, respectively. Intra-day precision ranged from 2.45% to 30.29%, and inter-day precision from 0.36% to 12.87%. Significant differences in the total amount of chitin and chitosan were observed among the insect products, processed insect products, and samples without any insect addition (p < 0.05).